Dynamics of Early Marriage Adjustment in Women Matched at a Young Age - Saudi, Rizky Rahmawati; Nur, Haerani; Jafar, Eka Sufartianinsih (Polteknik Ilmu Pemasyarakatan, 2024)
Early marital adjustment is very difficult to endure, especially for women who have been forced to marry because they were arranged in early-age. This research aims to determine dynamics of early marital adjustment in in early-age women in arranged marriages. The method used is a qualitative method with a phenomenological approach. The data was collected through in-depth interviews with four women who were married before the age of 18 and had been married for more than 10 years. Data analysis is conducted through four stages: epoche, phenomenological reduction, imaginative variation, and synthesis of meaning and essences. The result found that woman who arranged marriage in early-age generally experienced the dynamics of early marital adjustment through the five stages. Denial is shown through feelings of shock, sadness, fear, and rejection of marriage. Anger is shown through a decline in physical condition. Bargaining is shown through seeking help. Depression is shown through resignation and indifference towards marriage. Acceptance is influenced by supporting factors, namely the behavior and attitude of the husband, parents, carrying out the role of a wife, trying to convince oneself, readiness to become a parent, adjusting to the husband's family, fulfilling household needs, maintaining communication, and lowering the ego. The inhibiting factors are being unprepared for marriage and age differences with the husband. In the end, the respondents melted and began to accept their husbands due to the kindness, patience, and affection shown by them. The respondents have started to find happiness in their marriages. The implication of this research is that it is hoped that it can increase knowledge regarding the dynamics of early marital adjustment in in early-age women in arranged marriages.